Family communication patterns towards internalizing and externalizing problems in adolescents - Sawitri, Lintang Sekar; Widyasari, Dian Caesaria; Karmiyati, Diah; Syakarofath, Nandy Agustin; Mein-Woei, Suen; Marsuki, Nurfitriani (University of Muhammadiyah Malang, 2024)
Adolescence is when individuals face various developmental tasks that require them to do extensive exploration. Drastic changes and exploration processes during this period can cause internalizing and externalizing problems commonly found in adolescents, particularly when they lack support from the surrounding environment, especially from their parents and family. Family communication patterns are one of the important factors that can help adolescents navigate various developmental tasks while exploring optimally. This study measures the effects of the differences in consensual, pluralistic, protective, and laissez-faire family communication patterns on adolescents' internalizing and externalizing problems. Using a simple random sampling method, this comparative quantitative study involved 408 Muhammadiyah Junior High School students in East Java. The instruments used are the Strengths and Difficulties Questionnaire (SDQ) and The Revised Family Communication Pattern Instrument (FCP-R). The results of the one-way ANOVA test showed that family communication patterns have significant differences in internalizing problems, namely consensual laissez-faire (0.000) and pluralistic-laissez-faire (0.000). Likewise, in externalizing problems, family communication patterns revealed notable differences, namely in consensual-laissez-faire patterns (0.000). Of the various family communication patterns, only consensual laissez-faire and pluralistic laissez-faire can predict internalizing and externalizing problems. They must be tested further to ascertain the extent of their effects.